Ontogeny, morphology and taxonomy of the soft‐bodied Cambrian 'mollusc' Wiwaxia. (20th August 2013) - Smith, Martin R.; Lane, Phil
Abstract The soft‐bodied Cambrian organism Wiwaxia poses a taxonomic conundrum. Its imbricated dorsal scleritome suggests a relationship with the polychaete annelid worms, whereas its mouthparts and naked ventral surface invite comparison with the molluscan radula and foot. 476 new and existing specimens from the 505‐Myr‐old Burgess Shale cast fresh light on Wiwaxia's sclerites and scleritome. My observations illuminate the diversity within the genus and demonstrate that Wiwaxia did not undergo discrete moult stages; rather, its scleritome developed gradually, with piecewise addition and replacement of individually secreted sclerites. I recognize a digestive tract and creeping foot in Wiwaxia, solidifying its relationship with the contemporary Odontogriphus. Similarities between the scleritomes of Wiwaxia, halkieriids, Polyplacophora and Aplacophora hint that the taxa are related. A molluscan affinity is robustly established, and Wiwaxia provides a good fossil proxy for the ancestral aculiferan – and perhaps molluscan – body plan.